2022
DOI: 10.1145/3485874
|View full text |Cite
|
Sign up to set email alerts
|

Chatbots to Support Young Adults’ Mental Health: An Exploratory Study of Acceptability

Abstract: Despite the prevalence of mental health conditions, stigma, lack of awareness, and limited resources impede access to care, creating a need to improve mental health support. The recent surge in scientific and commercial interest in conversational agents and their potential to improve diagnosis and treatment seems a potentially fruitful area in this respect, particularly for young adults who widely use such systems in other contexts. Yet, there is little research that considers the acceptability of conversation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 91 publications
0
12
0
1
Order By: Relevance
“…The conversational nature of the intervention may have contributed to this high level of acceptability. Previous studies have identified that parents ( 53 ) and young adults ( 54 ) value interactive digital interventions in which they can write and talk in the same way they do with humans. Furthermore, the study was conducted during the COVID-19 pandemic, which was associated with increased levels of parental distress and child misbehavior in 2021 ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…The conversational nature of the intervention may have contributed to this high level of acceptability. Previous studies have identified that parents ( 53 ) and young adults ( 54 ) value interactive digital interventions in which they can write and talk in the same way they do with humans. Furthermore, the study was conducted during the COVID-19 pandemic, which was associated with increased levels of parental distress and child misbehavior in 2021 ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chatbots are a key technology poised to transform healthcare shortly. Chatbots are proposed as automated or semi-automated therapeutic and diagnostic tools [ 54 ]. The chatbot will conduct a short and easy health survey, especially in an emergency; when looking for a particular sign or pattern that can be used to diagnose a disease, the chatbot can react quickly or immediately to questions related to the patient’s healthcare [ 35 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to audio media, visual media, and audio–visual media, written media is the main thing in this telemidwifery menu because it is based on a chatbot in the form of a question-and-answer chat page. Chatbots , in particular, typically support text-based conversations or clickable responses and are designed to look like instant messaging apps [ 24 , 35 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…A avaliac ¸ão por meio de cenários é uma abordagem utilizada pela comunidade científica [Satyanarayanan 2001, Koulouri et al 2021. Foram criados dois cenários para a avaliac ¸ão do XPCodeHub.…”
Section: Avaliac ¸ãO Com Usuáriosunclassified